2020
DOI: 10.1016/j.ajoc.2020.100830
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis following combined cataract extraction and placement of an iStent trabecular bypass device

Abstract: Purpose To report a case of post-operative endophthalmitis following combined cataract extraction and minimally invasive glaucoma surgery with placement of the iStent drainage device. Observation An 87-year-old woman with a nuclear sclerotic cataract and primary open angle glaucoma underwent elective phacoemulsification cataract extraction with iStent placement. Surgery was complicated only by the inability to properly place the second iStent despite several attempts. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Although postoperative endophthalmitis following MIGS is uncommon, a higher risk of infection has been noted after the implantation of trabecular bypass devices, including the iStent inject (10 reported cases 1,6 excluding the current case), Xen Gel (Allergan Plc, Dublin, Ireland) (6 reported cases 1,7,8 ), and CyPass Microstent (Alcon, Fort Worth, TX) (1 reported case 1 ), compared with nonimplant MIGS procedures. The 10 prior-reported iStent-associated endophthalmitis cases isolated various Staphylococcus and Streptococcus species, none of which resulted in device removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although postoperative endophthalmitis following MIGS is uncommon, a higher risk of infection has been noted after the implantation of trabecular bypass devices, including the iStent inject (10 reported cases 1,6 excluding the current case), Xen Gel (Allergan Plc, Dublin, Ireland) (6 reported cases 1,7,8 ), and CyPass Microstent (Alcon, Fort Worth, TX) (1 reported case 1 ), compared with nonimplant MIGS procedures. The 10 prior-reported iStent-associated endophthalmitis cases isolated various Staphylococcus and Streptococcus species, none of which resulted in device removal.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 prior-reported iStent-associated endophthalmitis cases isolated various Staphylococcus and Streptococcus species, none of which resulted in device removal. 1,6 R. mucilaginosa-associated infections have been reported with various prosthetic devices in different organ systems, including prosthetic heart valves (most frequently), prosthetic hip implants, cerebral catheters, and peritoneal dialysis catheters. R. mucilaginosa aggressively colonizes implant surfaces with its ability to form biofilms on glass and plastic.…”
Section: Discussionmentioning
confidence: 99%
“…Chaves et al reported endophthalmitis after a combined cataract extraction and first-generation iStent placement in an elderly patient who struck her eye while instilling drops two days after the surgery. This patient eventually developed no light perception despite a negative culture and two intravitreal injections of antibiotics [ 7 ]. Lam et al reported a case of Rothia mucilaginosa endophthalmitis after phacoemulsification with insertion of two iStent injects, which progressed to retinal detachment requiring pars plana vitrectomy and removal of the IOL as well as iStents [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in 2020, the first report of endophthalmitis after iStent was published in the United States. This occurred 4 days following combined cataract surgery and iStent placement, and it resulted in no light perception vision 58. However, in a 2017 review and meta-analysis of MIGS outcomes, there were no cases of postoperative infection in the 30 studies that were examined 59.…”
Section: Infection In Glaucoma Surgeriesmentioning
confidence: 99%
“…This occurred 4 days following combined cataract surgery and iStent placement, and it resulted in no light perception vision. 58 However, in a 2017 review and meta-analysis of MIGS outcomes, there were no cases of postoperative infection in the 30 studies that were examined. 59 It is important to note that most of the individual studies were small and underpowered to identify a case of endophthalmitis assuming the rate of endophthalmitis more closely resembles that of cataract surgery alone.…”
Section: Rates Of Infection After Migsmentioning
confidence: 99%